Operational risk and financial performance of microfinance banks in Kenya - Ishmail, Daniel Mwasa; Memba, Florence; Muriithi, Jane (Full Length Research, 2022)
The aim of the study was to explore the effect of operational risk on financial performance of Microfinance banks in Kenya. The target population was MFBs regulated by Central Bank of Kenya (CBK). The study employed census method. Secondary data for thirteen (13) MFBs was collected from published annual reports for the period 2011-2019. The study employed explanatory research design. Unbalanced panel regression model was employed to examine the impact of independent variables on dependent variable using unbalanced panel data. The dependent variable, financial performance was measured by Return on Equity (ROE). The indicators of operational risk were Management Expense Ratio, Operational Expense Ratio, Ratio of Overheads to Total Earning and Cost Income Ratio The finding established that operational risk had significant and strong negative relationship financial performance of microfinance banks measured gauged with ROA. Similarly, the results revealed an insignificant weak relationship between operational risk and ROE. The model F statistics indicated operational risk had negative and significant influence ROA of Microfinance Banks in Kenya at 5% level of significance. In conclusion, the negative and significant relationship between operational risk and financial performance (ROA) implying that staff cost incurred in managing the organization has adverse effect on the profitability of MFBs. The study recommends MFBs should adopt and upgrade to information and communication technologies and management systems that minimize staff expense and overheads.
Keywords: Operational risk; Financial Performance; return on asset; return on equity; Microfinance Bank